IMF Research Bulletin, December 2010. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2010)
The Q and A in this issue features seven questions about emerging markets and the financial crisis (by Ayhan Kose); the research summaries are "Tax Revenue Response to the Business Cycle" (by Cemile Sancak, Ricardo Velloso, and Jing Xing) and "Banking Crisis Resolution: Was this Time Different?" (by Luc Laeven and Fabian Valencia). The issue also lists the contents of the second issue of the IMF Economic Review, Volume 58 Number 2; visiting scholars at the IMF during October-December 2010; and recent IMF Working Papers and Staff Position Notes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet